LncRNA NORAD targets miR-410-3p to regulate drug resistance sensitivity of osteosarcoma - Xie, Xin; Liu, Wenjun; Duan, Zhiyuan; Li, Xu; Zhang, Lide; Yang, Guanlin (Cellular and Molecular Biology, 2020)
The current experiment was performed to investigate the effect of LncRNA NORAD on the sensitivity of miR-410-3p to drug resistance of osteosarcoma cells. The cisplatin-resistant cell line HOS/DDP was induced; si-NC, si-NORAD, miR-NC, miR-410-3p, pcDNA-NC, and pcDNA-NORAD were transfected into HOS/DDP cells, respectively; record as a si-NC group, si-NORAD group, miR-NC group, miR-410-3p group, pcDNA-NC group, pcDNA-NORAD group; si-NORAD was co-transfected into HOS/DDP cells with anti-miR-NC, anti-miR-410-3p, recorded as an anti-miR-NC+si-NORAD group and anti-miR-410-3p+si-NORAD group. Real-time quantitative PCR (RT-qPCR) was used to detect LncRNA NORAD, miR-410-3p and multidrug resistance protein 1 (MRP1) mRNA expression levels; Western blot was used to detect cyclin D1 (CyclinD1), MRP1, phosphorylated (p-p65), phosphorylated IÐºBÎ± (p-IÐºBÎ±) protein expression; cell counting kit 8 (CCK-8) was used to detect cell viability; dual luciferase report assay to detect targeting relationship between LncRNA NORAD and miR-410-3p. Compared with osteosarcoma cells HOS, the expression levels of LncRNA NORAD, MRP1 mRNA and protein in osteosarcoma resistant cells HOS/DDP were significantly increased, and miR-410-3p expression levels were significantly reduced (P<0.05). Low expression of NORAD or high expression of miR-410-3p, CyclinD1, MRP1 expression levels were significantly reduced, the cell survival rate was significantly reduced, and the half inhibitory concentration of cisplatin was significantly reduced (P<0.05). LncRNA NORAD targets and regulates miR-410-3p, and low expression of miR-410-3p can reverse the effects of low NORAD expression on HOS/DDP cell proliferation and cisplatin resistance. Low expressions of NORAD, p-p65, p-IÐºBÎ± protein expression levels were significantly reduced; low expression of miR-410-3p could reverse the inhibitory effect of low NORAD expression on p-p65, p-IÐºBÎ± protein expression. Inhibition of LncRNA NORAD expression can inhibit the proliferation of osteosarcoma HOS/DDP cells through targeted regulation of miR-410-3p, increasing its sensitivity to cisplatin, and it may be related to the NF-ÎºB signaling pathway.